1995
DOI: 10.3109/01485019508987871
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Human Sperm Motility and Hyperactivation Components by Calcium, Calmodulin, and Protein Phosphatases

Abstract: The role of Ca2+, calmodulin, and protein phosphatases on motility and hyperactivation of noncapacitated, capacitating, and detergent-permeabilized reactivated human sperm was examined. In noncapacitated sperm, W7 inhibited percent motility (%MOT), curvilinear velocity (VCL), amplitude of lateral head displacement (ALH), and percent hyperactivation (%HYP) in an extracellular Ca2+ concentration-dependent manner (p < .05). However, in capacitating sperm, inhibition of motility by W7 was independent of external C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 59 publications
4
50
0
Order By: Relevance
“…At least some of the effects of calcium on the flagellum are likely to be achieved through CaM, because inhibition of CaM decreases sperm motility (White and Aitken 1989;Ahmad et al 1995;Si and Olds-Clarke 2000). Components of the PKA pathway can restore motility to CaM-inhibited sperm if the glycolytic products pyruvate and lactate are present in the medium (our unpublished data).…”
Section: Downstream Components Of Calcium Signallingmentioning
confidence: 99%
“…At least some of the effects of calcium on the flagellum are likely to be achieved through CaM, because inhibition of CaM decreases sperm motility (White and Aitken 1989;Ahmad et al 1995;Si and Olds-Clarke 2000). Components of the PKA pathway can restore motility to CaM-inhibited sperm if the glycolytic products pyruvate and lactate are present in the medium (our unpublished data).…”
Section: Downstream Components Of Calcium Signallingmentioning
confidence: 99%
“…Researchin several laboratories supportsthe ideathatreversibleproteinphosphorylation is associated with initiation andmodulationof sperm motility (1)(2)(3)(4)(5). Many studies aimed at examining the intracellular signaling pathways that initiate the activation of flagellar motility have relied on detergent-permeabilized sperm reactivated with exogenous 32p-ATP (2,6).…”
mentioning
confidence: 99%
“…Metabolic inhibitors or extended incubations at cold temperatures prior to reactivation of motility have been used to try to reverse the effects of background motility (3,9,10). However, these methods depend on endogenous enzyme activities that may reverse the signals originally induced in the background motility (3,(11)(12)(13) In addition, the following buffers were used: motility assay buffer (MAB), contained 1 mg/ml BSA in ASW; and non-motility assay buffer (NMAB), had 1 mg/ml BSA in MSSB or SSB.…”
mentioning
confidence: 99%
“…Calcium and its channels control the transition from symmetric to asymmetric flagella waveforms (Si, 1997) as an intracellular regulator of Ca 2+ function and have been identified both in the head and flagellar parts of spermatozoa (Tash and Means, 1983) and are believed to be a major signal transducer in Ca 2+ regulating motility. Calmodulin antagonist or lack of melatonin caused a reduction in VCL and ALH and it is related with mitochondrial membrane potential and mobility & velocity of the spermatozoa (Ahmad et al, 1996). These results suggested that melatonin has enhanced the regulatory role of Ca 2+ /calmodulin pathway in sperm motility and velocity parameters including VCL and ALH in liquid storage of mithun semen.…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 65%